Visualized strain profile in the process of crystal ion slicing of LiTaO3. (15th April 2016) - Ma, Changdong; Lu, Fei; Xu, Bo; Fan, Ranran
Abstract: LiTaO3 samples are implanted with 190KeV He and 110 KeV H with fluences in the range 2  ×  10 16 –6  ×  10 16 cm −2 at room temperature. Lattice damage and strain caused by ion implantation and their change with annealing temperature are characterized by Rutherford backscattering spectrometry, high resolution x-ray diffraction and transmission electron microscopy. Strain distributions are illustrated by comparing simulated x-ray diffractive curves to the experimental results. In contrast to a broad strain distribution in H implanted samples, strain distribution is very concentrated in He-only or He-first co-implanted samples. Microfractures are caused in He-first samples due to severe lattice damage and large lattice strain. The strong coalescence effect of He ions in co-implanted LiTaO3 is analyzed and the mechanism of built-up high normal strain is proposed.